Effect of bleaching on the shear bond strength of the enamel - Thiago Arruda; Luís Guilherme Sensi; Fabiano Carlos Marson (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the effect of dental bleaching on the shear bond strength of enamel. Methods: Fifty molars were selected and divided into five groups (n=10); G1-without bleaching (control); G2-bleached with 10% carbamide peroxide and restored 24h later; G3-bleached with 10% carbamide peroxide and restored seven days later; G4-bleached with 35% hydrogen peroxide and restored a 35% and restored 24h later; G5-bleached with 35% hydrogen peroxide and restored a 35% and restored seven days later. During the 24h and 7-day intervals the test specimens remained stored in artificial saliva, after which the restorative procedures were performed on the enamel. Results: The microshear bond strength test indicated the following results in MPa (ANOVA and Tukey post-hoc): G1-43.15 a (±5.19); G2-31.34 ab (± 4.41); G3-36.66 ab (± 3.11); G4-22.87 c (±3.76) and G5-35.67 ab (± 4.64). Conclusion: Groups G1, G2, G3 and G5 showed no statistical difference and Group G4 (bleached with 35% hydrogen peroxide and restored 24h later) showed diminished bond strength between the bleached enamel and resin composite.